The Role of Internal Control Unit (SPI) To Achieve Good University Governance - Salman Alfarisy Totalia; Budi Wahyono; Triyanto Triyanto; Muhtar Muhtar; Dowes Ardi Nugroho (STAI Hubbulwathan Duri, 2022)
To achieve the principle of good university governance, the use of state finances must be managed orderly, regulatory, efficiently, economically, effectively, transparently, responsibly and having fair sense and properly from the planning, implementation and its accountability process. In reality, not all universities are able to achieve the good university governance principles. This article aims to find out how the role of Internal Control Unit (SPI) in achieving the principles of good university governance in universities. We used qualitative method to find out how the role of SPI in achieving the good university governance principles. The informants in this study were selected by purposive sampling. Data collection was carried out by interview and the data analysis technique was carried out by data reduction, data presentation and making conclusion. The conclusion of this research was that the SPI had important role in the effort to achieve the principle of good university governance. However, there were some problems related to ineffectiveness of the SPI's role. The results of this research were to provide recommendation as well on the importance of research related to the effectiveness of internal control in higher education.